Prispevek porabskih Slovencev k osamosvajanju Slovenije - Munda Hirnök, Katalin (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2007)
The analysis of the documents, stored in the archives of the Association of Slovenes in Hungary, i.e. articles, published mostly in the papers Porabje and Vestnik, as well as memory notes, proves that the Slovenes of Porabje significantly contributed to the independence of Slovenia. The first part of the article highlights different efforts of the Porabje Slovenes for the international recognition of Slovenia, while the second part is mostly focused on the responses of Hungarian politics to the open letter of the president of the Association of Slovenes in Hungary (addressed to all major Hungarian politicians, published in all the major Hungarian printed media) in the context of the Hungarian foreign policy before and after the break-up of Yugoslavia and at the proclamation of independent Slovenia. Also stated are the official standpoints of the Vas and Zala counties.
Keywords: Slovenia; Slovenija; osamosvojitev; mednarodno priznanje; Hungary; Madžarska; zamejski Slovenci; Hungarian Slovenes; porabski Slovenci; Zveza Slovencev na Madžarskem